Analisis Persepsi Siswa SMP Negeri 6 Lubuklinggau Terhadap Keanekaragamaan Hewan Vertebrata - Amelia vega Amel; Destien Atmi Arisandy; Mareta Widiya (JBIOEDRA: Jurnal Pendidikan Biologi, 2025)
This study aims to analyze the perceptions of students at SMP Negeri 6 Lubuklinggau regarding the diversity of vertebrate animals, focusing on three aspects: knowledge, attitude, and behavior. The research employed a descriptive quantitative method with the population consisting of all seventh and eighth-grade students in the 2024/2025 academic year. Data were collected using a closed-ended questionnaire designed around the three main aspects, and were analyzed by calculating the mean score and percentage through simple frequency distribution. The results show that the overall average score of students’ perceptions is 3.34 with a percentage of 83.55%, categorized as very good. In terms of knowledge, students demonstrated a strong understanding of the basic classification of vertebrates (highest score 3.55), though many still struggled to distinguish characteristics among different groups (3.19). For attitudes, students responded positively to learning, particularly appreciating the enjoyable teaching methods used by teachers (3.52), although some still found vertebrate concepts difficult to grasp (3.19). Regarding behavior, students showed empathy by having experiences of helping injured animals (3.41), but relatively few had opportunities to observe vertebrates directly outside of school (3.27). Overall, the findings indicate that students’ perceptions of vertebrate diversity are highly positive. However, improvements are still needed through the use of visual media, field observations, and guidance in utilizing credible digital learning resources.